Cover Image. Issue 2 (14th March 2019) - Li, Jianda; Wang, Jinbao; Liu, Yueyue; Yang, Jie; Guo, Lihui; Ren, Sufang; Chen, Zhi; Liu, Zhaoshan; Zhang, Yuyu; Qiu, Wenbin; Li, Yubao; Zhang, Shujin; et al.
Abstract : The cover image is based on the Original Article Porcine reproductive and respiratory syndrome virus NADC30‐like strain accelerates Streptococcus suis serotype 2 infection in vivo and in vitro, by Jianda Li et al., DOI 10.1111/tbed.13072 .